Using camera‐trap photographs to identify individual fox squirrels (Sciurus niger) in the Southeastern United States. (27th August 2015) - Tye, Courtney A.; Greene, Daniel U.; Giuliano, William M.; Mccleery, Robert A.
ABSTRACT Fox squirrels (Sciurus niger) in the southeastern United States have been difficult to survey because of their sparse distribution, large home ranges, and low capture success. Remote cameras have proven to be an effective tool for surveying larger mammals, including identifying individual animals using their unique markings. To test whether cameras can be used to identify individual fox squirrels in the southeastern United States, we 1) inspected digital photographs of fox squirrels; 2) identified variable pelage features for individual identification; 3) tested the ability of wildlife students and professionals to identify individuals; and 4) evaluated whether training improved participants' ability to identify individuals. We found that fox squirrels could be individually identified using a combination of sex and 10 variable pelage features, including the color morph, presence of an eye ring, distribution of white on the rostrum, and facial markings. In total, we developed ≥25, 920 possible combinations of features to identify southeastern fox squirrels. We found survey participants were capable of identifying fox squirrels without training, but their average ability to do so increased significantly from 73.6% to 80.3% after training (t[df = 106] = 5.068, P < 0.001). The results from this study demonstrate that camera‐trapping, particularly when combined with training that focuses on which features vary between individuals, provides an alternative method to live‐trapping for population‐level studies of southeastern fox squirrels. © 2015 The Wildlife Society.